ANALISIS PENGARUH INDUSTRI PERHOTELAN DAN RESTORAN KOTA BOGOR TERHADAP PENDAPATAN ASLI DAERAH 2007-2016 - Sekti Rahardjo; Dina Mayasari Soeswoyo (Eduturisma, 2017)
This study aims to determine the influence of the hospitality industry and restaurants Bogor City against Local Revenue (PAD). Research method using quantitative approach with multiple linear regression analysis backward method. Technique of collecting data by observation, interview, documentation and literature study. The research subjects are the Regional Revenue Service and the Bogor City Tourism Office with the object of Tax Hotel and Restaurant Tax Data and the Bogor City PAD data. The result of this research is restaurant industry of Bogor City with its restaurant tax by partially positive and significant influence to PAD. Hotel industry through tax contribution does not affect the PAD of Bogor City, but simultaneously the hospitality industry and restaurants Bogor Citypositively and significantly affect the PAD Bogor City.